Effect of nutrition on the body temperature and relative organ weights of broilers - Julyana Machado da Silva Martins; Evandro de Abreu Fernandes; João Paulo Rodrigues Bueno; Carolina Magalhães Caires Carvalho; Fernanda Heloisa Litz; André Lucas Silva Masculi; Naiara Simarro Fagundes; Marina Cruvinel Assunção Silva; Márcia Marques Silveira; Cíntia Amaral Moraes (Semina: Ciências Agrárias, 2015)
The objective of this study was to evaluate the effect of different nutritional plans on the body temperature and organ biometrics in male and female broilers, of two ages. Here, 1,700 birds were used (850 males and 850 females) in a completely randomized design composed of five treatments (- 3%, - 1.5%, reference, + 1.5% and + 3%), with 10 repetitions, totaling 50 experimental units; the reference treatment based on nutritional and energy levels indicated in previous studies was calculated from this. At 35 and 42 d, the temperatures of the wing, head, shin, back, and cloaca in males and females were measured separately, and the average surface and body temperature were calculated. At 42 d, relative weights of the gizzard, liver, heart, and small intestine were calculated. The temperatures of the wings, back, and cloaca, and consequently the average surface temperature and body temperatures, were not affected by nutritional plans. Effects of increasing the nutritional and energy levels were observed on liver weights, the gizzard, and the small intestine. We conclude that the nutritional plans did not affect body temperature. Males had higher body temperatures than females. Body temperature increased with increase in age, and the increase in the nutritional plans increased liver weight and reduced the gizzard weights.